Pengembangan Media Big Book Untuk Meningkatkan Hasil Belajar Pada Materi Negaraku Indonesia Siswa Kelas IV SDN Pengadegan 03 Pagi Jakarta Selatan - Rosiani, Indi Aprilia; Ritonga, Rudi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This development research aims to develop Big Book learning media to improve the learning outcomes of fourth grade elementary school students. The type of research used is ADDIE model development research which goes through five stages, namely analysis, design, development, implementation and evaluation. Data collection was carried out using validation techniques and questionnaires. The validity of Big Book media is obtained through validation results from design experts, material experts and language experts. The design expert's validation results obtained a percentage of 96% (very valid). Meanwhile, the results from material expert validation obtained a percentage of 94% (very valid). Meanwhile, the results from validation by language experts obtained a percentage of 96% (very valid). Media practicality was obtained from student questionnaires on a small scale, medium scale and large scale. In the results of the small scale student questionnaire, the percentage was 93.6%. Meanwhile, the results of the medium scale student questionnaire obtained a percentage of 91.3%. Meanwhile, the results of the large-scale student questionnaire obtained a percentage of 90.8%. All student questionnaire results were stated to be very practical. The results of media effectiveness were obtained from student responses in the form of pretest and posttest on a small scale, medium scale and large scale. The small scale score results obtained a percentage of 50.8% pretest, 89.1% posttest and N-Gain 0.77. Meanwhile, the medium scale score results obtained a percentage of 54.6% pretest, 90.8% posttest and N-Gain 0.79. Meanwhile, the large scale score results obtained a percentage of 57.2% pretest, 92.6% posttest and N-Gain 0.82. Big Book media was declared effective. Based on the results of the analysis, it can be concluded that the Big Book media for improving the learning outcomes of fourth grade elementary school students is valid, practical and effective for use in classroom learning.